2021
DOI: 10.1210/endocr/bqab079
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibitors as Calorie Restriction Mimetics: Insights on Longevity Pathways and Age-Related Diseases

Abstract: SGLT2 inhibitors induce glycosuria, reduce insulin levels, promote fatty acid oxidation and ketogenesis. By promoting a nutrient deprivation state, SGLT2 inhibitors upregulate the energy deprivation sensors AMPK and SIRT1, inhibit the nutrient sensors mTOR and insulin/IGF-1, and modulate the closely-linked HIF-2α/HIF-1α pathways. Phosphorylation of AMPK and upregulation of adiponectin and PPAR-α favour a reversal of the metabolic syndrome which have been linked to suppression of chronic inflammation. Downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 258 publications
1
28
0
1
Order By: Relevance
“…21 On the other hand, a decrease in IGF signaling and subsequent phosphoinositide-3-kinase/Protein kinase (PI3K/Akt) activation may shift the metabolic focus from growth toward maintenance and cellular repair. 21,28,29 This can in turn attenuate senescence-related cardiac hypertrophy and interstitial fibrosis, inflammation and oxidative stress which are likely protective in HFpEF. 21 Decreased IGF activation could also decrease tumorogenesis or cancer progression and may explain in part the association between lower circulating IGF and survival in older cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…21 On the other hand, a decrease in IGF signaling and subsequent phosphoinositide-3-kinase/Protein kinase (PI3K/Akt) activation may shift the metabolic focus from growth toward maintenance and cellular repair. 21,28,29 This can in turn attenuate senescence-related cardiac hypertrophy and interstitial fibrosis, inflammation and oxidative stress which are likely protective in HFpEF. 21 Decreased IGF activation could also decrease tumorogenesis or cancer progression and may explain in part the association between lower circulating IGF and survival in older cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…), as well as by inhibiting insulin/IGF-1 signaling, ultimately leading to decreased circulating glucose and amino acids. Therefore, SGLT-2is appear to mimic nutrient deprivation states, thus attenuating cellular ageing and stress, and to alter cellular metabolic programming through a dormancy state with increased production of ketone bodies ( 90 ).…”
Section: Sglt-2 Inhibitorsmentioning
confidence: 99%
“…SGLT are active glucose co-transporters in the renal tubules preventing glycosuria by means of filtered glucose reabsorption along with sodium into the circulation. SGLT2, which is located almost exclusively in the S1 segment of the proximal renal tubules, carries out 90% of glucose resorption, whereas SGLT1, which is located distally in the S3 segment of the proximal tubule, reabsorbs the remaining 10% of filtered glucose [97]. SGLT1 is also located in the small intestines, heart, skeletal muscles, pancreas, and salivary glands.…”
Section: Prevention Of New-onset Heart Failure In Diabetesmentioning
confidence: 99%
“…Despite SGLT2 localization predominantly in the renal tubules, SGLT-2i have important systemic effects [97]. In this regard, clinical studies have shown that SGLT-2i not only improve glycemic control but additionally reduce major adverse CV events and hospitalization for heart failure (HF) and improve outcome in CKD, both in patients with DM and those without DM [98,99].…”
Section: Prevention Of New-onset Heart Failure In Diabetesmentioning
confidence: 99%